DEFORMASI KEBIJAKAN PENANGAN ANAK JALANAN KOTA SEMARANG - Indra Kertati, M.Si (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
Street children in Semarang become major problem nowadays. Spacious distribution and high vulnerability is one of the main concern. The problem of street children is being complicated because of the network complexity. Street children are now in three scopes of the regional government such as the police department, the community, and the environment. Semarang government already has Regional Regulation number 5 of 2014 which regulates the handling of street children. The content of the Regional Regulation has fulfilled the needs in handling street children. However, this policy has not been able to work effectively because there are several verse that are still being debated both in the community and in the local government. The step that must be carried out is deforming the Regional Regulation by passing the Mayor Regulation as a more operational policy. In the perspective of the implementation context of handling street children, five strategies are being used. These strategies are prevention, service, advocacy, protection and rehabilitation.